The heterosis value of economically valuable traits in the multi-row hybrids F1 of spring barley obtained by saturating crossings - N. A. Kryuchkova; G. А. Murugova; А. G. Klykov (Зерновое хозяйство России, 2021)
The current paper has presented the analysis results of the value of heterosis and the degree of phenotypic dominance of hybrids F1 obtained by saturating crossings of two-row and multi-row spring barley forms. The purpose of the study was to determine the value of heterosis and the degree of phenotypic dominance of the main quantitative traits of the multi-row hybrids of spring barley. The study was carried out in the laboratory for grain crops and groats breeding of the FSBSI FRC of Agrobiotechnologies of the Far East named after A. K. Chayka. There were studied 68 varieties of multi-row spring barley forms selected from the world collection of IPI of various ecological and geographical origin. The two-row varieties ‘Primorsky 98’, ‘Primorsky 44’, ‘Primorsky 89’, ‘Tikhookeansky’ and ‘Vostochny’ developed by FSBSI FRC of Agrobiotechnologies of the Far East named after A. K. Chayka were taken as maternal forms. Four multi-row barley varieties ‘Kazminsky’ (Khabarovsk Territory), ‘Peguis’ (Canada), ‘Kolchan’ (Altai Territory), ‘07N1’ (China) with valuable economic traits were taken as a paternal form. There was conducted a five-fold backcrossing of hybrids with paternal forms and there were selected the populations of multi-row genotypes. The most of the hybrids F1 manifested their heterosis simultaneously according to four traits, productive tillering, number of grains per main head, grain weight per main head, and grain weight per a plant. Only two hybrids ‘Primorsky 98 x Kolchan’ and ‘Primorsky 89 x Peguis’ showed a depression. There was identified heterosis by the traits ‘number of grains per main head’, ‘grain weight per main head’ in all hybrids. When analyzing the inheritance of the trait ‘grain weight per a plant’, there was established overdominance of this trait at the highest values of the hybrids ‘Tikhookeansky x Peguis’ (9.7) and ‘Primorsky 44 x 07N1’ (5.2), the heterosis degree was 50.4% and 82.2%, respectively. There has been established that three hybrids ‘Primorsky 98 x 07N1’, ‘Primorsky 44 x 07N1’, ‘Tikhookeansky x Peguis’ can belong to the most promising ones.